Motherhood and its representations in contemporary Iraqi painting (The Peerian Journal, 2025)
The research aims to dismantle, analyze and understand the artistic, aesthetic and expressive aspects of maternity drawings, to study the motives behind future additions in contemporary Iraqi painting, and to employ the vocabulary that through their interaction achieves the artist's vision, as well as the need to study the concepts of contemporary Iraqi painting. The study plays an important role in marking the map of contemporary Iraqi plastic creativity through artistic achievement and unique experiences and approaching the artist’s self-awareness and his artistic personality through the two-dimensional painting to reach the visual text matching of his reality, negatively and positively, in form or content, and striving to shed light on the features of Iraqi society and its reflection on motherhood and study their cases. The research sample models revealed a clear diversity in the style of artworks such as the realistic style as in the samples’ model (6), the symbolic as in the samples’ model (5), the abstract as in the samples’ model (2), and the expressive as in the samples’ model (1, 4) . Maternity appeared through the expression of color and its psychological, symbolic and idiomatic connotations, mechanisms of saturation, impoverishment, transparency and aesthetic color relations, as in the sample model (2) Baghdadi women, as the painting relied on the method of abstraction and on colors according to what is included in the subject and in Figure 17 in the third topic. Chapter Two Dark colors appear with moonlight to highlight the classic realistic depiction using the color harmony in the painting. The sample is a model (7) The drawing is based on the expression of resemblance, in which the forms have evolved from abstract to overlapping structural units that are superior to the triangle, which agree with the identity through style and material